A Technique for Preoperative Estimation of Resection Weight in Vertical Reduction Mammoplasty Using 2 Breast-Specific Surface Measurements. (June 2018) - Archual, Anthony J.; Payton, Jesse; Black, Jonathan S.
Abstract : Abstract: Insurance authorization of reduction mammoplasty can be a challenging process. Despite copious evidence of the benefits of this operation and evidence that specimen weight does not correlate with symptomatic relief, most insurance providers require estimated resection weights. Many formulas and techniques to predict resection weight are inconsistent or not specific to the vertical technique. This study describes a simple method for generating a surgeon-specific equation for accurately predicting vertical reduction mammoplasty resection weight using 2 breast surface measurements.